2017
DOI: 10.15171/ehem.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

An assessment on dispersion of carbon monoxide from a cement factory

Abstract: Background: Modeling the dispersion of pollutants from factory stacks addresses the problem of matching emissions of a cement plant with the capacity of the environment to avoid affecting the environment and society. The main objective of this study was to simulate the dispersion of carbon monoxide (CO) from the main stack of a cement plant in Doroud, Iran using SCREEN3 software developed by the US Environmental Protection Agency (US EPA). Methods: Four samplings were conducted to measure the concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Similar result study in Iran shown that the worst condition occurred in spring in an unstable condition in which the maximum concentration of pollutant measured near the cement plant was at a higher level than in the other seasons. 25 CO and TSP have harmful effects on human health. When inspired, environmental CO diffuses rapidly across the alveolar capillary membrane and binds to hemoglobin, forming carboxyhemoglobin (COHb).…”
Section: Discussionmentioning
confidence: 99%
“…Similar result study in Iran shown that the worst condition occurred in spring in an unstable condition in which the maximum concentration of pollutant measured near the cement plant was at a higher level than in the other seasons. 25 CO and TSP have harmful effects on human health. When inspired, environmental CO diffuses rapidly across the alveolar capillary membrane and binds to hemoglobin, forming carboxyhemoglobin (COHb).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon monoxide is a poisonous gas for humans and animals and also has adverse effects on the environment [2] Regarding the concentration ------------------------of carbon monoxide in the exhaus t air of Iran's indus tries, several inves tigations have been carried out, for example, in 2010, Junadi et al inves tigated the exhaus t of was te incinerators of several hospitals in Hamedan city, and the highes t concentration of carbon monoxide reported as 1041 ppm, which 10.4 times the s tandard of the Environmental Organization in 2002 [4]. Also, in another s tudy, Guderzi et al inves tigated the pollutants from cement indus tries in Lores tan city, and based on the results, the highes t concentration of carbon monoxide is related to winter and spring seasons and is equal to 630 ± 53.04 and 2378 ± 76 ppm, respectively, which are higher than the permissible exposure limit [5]. About 95% of the absorbed carbon monoxide is easily combined with hemoglobin to form carboxyhemoglobin.…”
Section: Introductionmentioning
confidence: 99%